2023
DOI: 10.1001/jamaneurol.2022.3902
|View full text |Cite
|
Sign up to set email alerts
|

Widening the Spectrum of Risk Factors, Comorbidities, and Prodromal Features of Parkinson Disease

Abstract: ImportanceThe prodromal phase of Parkinson disease (PD) may last for more than 10 years. Recognition of the spectrum and occurrence of risk factors, comorbidities, and prodromal features of PD can increase understanding of the causes and development of the disease and help identify individuals at risk.ObjectiveTo identify the association of a subsequent diagnosis of PD with a range of risk factors and prodromal features, including lifestyle factors, comorbidities, and potential extracerebral manifestations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 85 publications
2
35
1
1
Order By: Relevance
“…A previous study by Stanković and colleagues found that 71% of early PD patients, classified as Hoehn and Yahr (H&Y) stage I, reported having autonomic symptoms (2). Autonomic dysfunction may also be a prodromal manifestation of PD, with early autonomic features predicting a faster rate of PD progression (3)(4)(5). Furthermore, pathological studies have shown the presence of alpha-synuclein deposition within the nuclei of autonomic plexi, which has been found to correlate with accelerated cell death in the autonomic nervous system (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study by Stanković and colleagues found that 71% of early PD patients, classified as Hoehn and Yahr (H&Y) stage I, reported having autonomic symptoms (2). Autonomic dysfunction may also be a prodromal manifestation of PD, with early autonomic features predicting a faster rate of PD progression (3)(4)(5). Furthermore, pathological studies have shown the presence of alpha-synuclein deposition within the nuclei of autonomic plexi, which has been found to correlate with accelerated cell death in the autonomic nervous system (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…We found a higher risk of PD for one behavioral risk factor than for two or more behavioral risk factors. In general, previous studies have shown a positive association between alcohol abuse 42 and PD and traumatic brain injury 43 and PD, whereas there is a negative association between nicotine abuse and PD 36,44 . By combining risk factors with opposite effect directions, effect sizes of the index variable should be viewed with caution.…”
Section: Discussionmentioning
confidence: 82%
“…Associations between epilepsy and PD [ 3 , 4 ] and between restless legs syndrome and PD [ 15 , 16 ] have already been reported in the past. The prevalence of restless legs syndrome is increased in PD patients compared to the general population, and both epilepsy and restless legs syndrome have been reported as an early clinical feature of PD [ 16 , 17 ]. Furthermore, pain is a common non-motor symptom of PD, and neuropathy is increased in PD patients, including in the prodromal phase [ 7 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%